Anaerobic power and repetitive muscle work capacity of older elite and developing young basketball players - Paulauskas, R.; Dadeliene, R.; Paulauskiene, R.; Skernevicius, J. (Education. Physical training. Sport, 2012)
Research background and hypothesis. Players need to repeat performance of highly intensive work for a particular time combining it with rest intervals. The muscle power and anaerobic repetitive muscle work capacity of elite basketball players is higher than those in young athletes. Research aim was to investigate anaerobic power and repetitive muscle work capacity of older elite (n = 13) and young basketball players (n = 12) and to carry out comparative analysis of indicators in these groups. Research methods. During competition period, laboratory 5 × 6 s repeated effort test with rest intervals of 24 s was employed. The average indicator of power during each work interval was provided and fatigue index was calculated. Three minutes after the physical load, the concentration of lactate in the blood was measured. Research results. A statistically significant difference was observed for absolute muscle power of elite and young basketball players in the first sprint (p < 0.004) The research on relative indicators for one kilogram of the body mass showed that the power of elite (13.06 W·kg-1) and young players (11.74 W/kg) did not differ statistically (p < 0.09). The fatigue index investigated in both groups did not differ (p < 0.77). Discussion and conclusions. The research revealed that relative indicators of muscle power of elite basketball players did not significant differ from those of young athletes. The same anaerobic repetitive muscle work capacity was observed in both groups. It was established that the concentration of lactate in the blood increased after physical load more than to 9 mol/l and did not differ in the two groups. This means that working for 6 seconds at maximum strength and relaxing 4 times longer, repeating this work five times, PCr is not enough for ATP resynthesis and, therefore, anaerobic glycolic reactions are activated.